How can Cleaner Production practices contribute to meet ISO 14001 requirements? Critical analysis from a survey with industrial companies - de Oliveira, José Augusto [UNESP]; Silva, Diogo Aparecido Lopes; Guardia, Mariana [UNESP]; do Nascimento Gambi, Lillian; de Oliveira, Otávio José [UNESP]; Ometto, Aldo Roberto [UNESP] (Springer Nature, 2017)
The companies’ needs to adopt changes in their way of production to maximize the environmental performance required by their stakeholders, and at the same time, to maximize their economic and market performance, have made them seek for environmental strategies and certifications. In this sense, the Cleaner Production and the Environmental Management System based on ISO 14001 have been, respectively, presented, since the main objective of this research is to identify and analyze Cleaner Production contributions to comply with ISO 14001 requirements. For such, a survey research has been carried out in Brazilian industrial companies certified by ISO 14001. We have identified the main performance factors by leading practices and variables of Cleaner Production that contribute to the compliance with the standard requirements by companies. Thus, it has been noted that Cleaner Production is an important strategy for the preparation of companies for certification as well as for improving their environmental performance.
Keywords: Brazilian industrial companies; Cleaner Production; Compliance; Environmental Management System; ISO 14001